Contributions of the historical-cultural theory in the pedagogical practice of literacy teachers in the Region of Pantanal Sul-Mato-Grossense - Souza, Regina Aparecida Marques de; Rodrigues, Geruza Soares de Souza Papa (Revista Hipótese, 2018)
This article has the purpose of presenting the contributions of the Historical- Cultural Theory in the pedagogical practice of teachers / literacy teachers in the region of the Pantanal Sul-mato-grossense, with the objective of favoring activities that allow the child to experience the social function of writing In the cycle of literacy, providing the construction of a citizenship that goes beyond meeting social demands, who know how to think and interfere on reality in a critical way, from the formation of the text producer and the reader / The. We seek to apprehend the contributions of this theory in the formation of teachers / literacy teachers, through a methodology subsidized by studies that approach the theme, based on the historical-cultural theory. The results are still partial, but already they present us that in the organization of the pedagogical practice we have a mixture of conceptions that move from a traditional model covered with the conceptions of literacy and literacy.